Plasminogen Activator Inhibitor‐1 Controls Bone Marrow‐Derived Cells Therapeutic Effect Through MMP9 Signaling: Role in Physiological and Pathological Wound Healing123. (18th June 2012) - Ebrahimian, Teni G.; Squiban, Claire; Roque, Telma; Lugo‐Martinez, Haydee; Hneino, Mohamad; Buard, Valerie; Gourmelon, Patrick; Benderitter, Marc; Milliat, Fabien; Tamarat, Radia
Abstract: We assessed the role of plasminogen activator inhibitor‐1 (PAI‐1) and matrix metalloproteinase 9 (MMP9) in wound healing process and in the bone marrow mononuclear cells (BMMNC)‐related effects on physiological and pathological wound healing. A full thickness excision wound was created by removal of the skin on the midback of irradiated and nonirradiated animals. Angiogenesis and re‐epithelialization were markedly increased in PAI‐1−/− mice compared to wild‐type (WT) animals. We revealed high MMP activity in tissue of PAI‐1−/− animals. Of interest, the wound healing process was reduced in PAI‐1−/−:MMP9−/− animals compared to PAI‐1−/− mice, suggesting a key role of MMP9 in beneficial effect of PAI‐1 deficiency on wound closure. To unravel the role of PAI‐1 in BMMNC relative effects, mice were treated with or without local injection of BMMNC isolated from WT, PAI‐1−/−, and PAI‐1−/−: MMP9−/− animals for 14 days (10 6 cells, n = 6 per group). In WT nonirradiated mice, transplantation of BMMNC isolated from PAI‐1−/− animals enhanced wound formation when compared with WT BMMNC. BMMNC differentiation into cells with endothelial phenotype was enhanced by PAI‐1 deficiency. These effects were abrogated in PAI‐1−/−:MMP9−/− and MMP9−/− BMMNC. In addition, using chimeric mice, we demonstrated that PAI‐1 deficiency environment increased the BMMNC‐GFP recruitment to the wound site, whereas this effect was abrogated when using PAI‐1−/−:MMP9−/− BMMNC. PAI‐1 deficiency, at least through MMP9 upregulation, enhanced wound healing and BMMNC therapeutic potential in irradiated and nonirradiated animals. Stem Cells 2012;30:1436–1446